Parametric Study for Runner Modification of Die Casted Part with Venting Systems - JASMINE ANAK, JENDIA (UNIVERSITI MALAYSIA SARAWAK, 2023)
High pressure die casting (HPDC) creates complex components by injecting the molten metal inside the cavity at high pressure. Failure in die casting may reduce product mechanical properties, surface quality, and life cycle. This research aimed to investigate the die-casting process of an inspection instrument–test piece using parametric study and computational fluid dynamics (CFD) analysis. Parameters used in the die-casting process are important since they affect the quality of molten flow inside the cavity. Thus, a parametric study is conducted to investigate the optimum parameter used in the die-casting process of the test piece. Based on the parametric analysis, the higher the velocity, the higher the pressure of molten metal inside the cavity, which means low air entrapment, hence, high volume of molten metal leads to high temperature. Cavity pressure lower than atmospheric pressure also could help to suck the air out from the molten metal, however, too low cavity pressure also could lead to backflow that could trap more air. In this analysis, the optimized parameters are cavity pressure of 10,000 Pa and inlet velocity of 3.00 m/s. This research also investigated the effect of runner gating system design optimization in reducing gas porosity. This research proposed a new runner design named outward curvature runner with air vents that have improved the velocity and temperature distributions in reducing air entrapment and thermal differences according to CFD analysis results. This research also aims to give die-casting manufacturers ideas for reducing manufacturing costs and improving productivity.